The Epidemiology of Salmonella enterica Outbreaks in Australia, 2001–2016 - Ford, Laura; Moffatt, Cameron R. M.; Fearnley, Emily; Miller, Megge; Gregory, Joy; Sloan-Gardner, Timothy S.; Polkinghorne, Benjamin G.; Bell, Robert; Franklin, Neil; Williamson, Deborah A.; Glass, Kathryn; Kirk, Martyn D. (Frontiers in Sustainable Food Systems, 2018)
Salmonella enterica is an important cause of foodborne illness in Australia, regularly causing high-profile outbreaks involving commercially-available foods. We used the national register of foodborne outbreaks to review the transmission pathways, settings, serotypes, and food vehicles of Salmonella outbreaks in Australia between 2001 and 2016. We examined trends over time of implicated food vehicles in outbreaks where there was statistical, microbiological, or descriptive evidence. Of the 990 Salmonella outbreaks reported, 79% (778/990) were suspected or confirmed to have been transmitted through contaminated food. Of these, 61% (472/778) occurred in food premises and 84% (656/778) were caused by Salmonella Typhimurium. Eggs and egg-containing foods were the most frequently identified food vehicle. Outbreaks due to egg-based sauces and Vietnamese style sandwiches, which often contain pâté and raw egg butter, increased, while outbreaks due to poultry meat, beef, pork, and other desserts had a decreasing trend from 2001 to 2016. Identifying food vehicles and the Salmonella serotypes causing outbreaks in Australia provides important evidence for food regulation strategies and control measures.